2008
DOI: 10.1128/jcm.02158-07
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genotyping of Campylobacter Species by Use of PCR and High-Throughput Mass Spectrometry

Abstract: In this work we report on a high-throughput mass spectrometry-based technique for the rapid highresolution identification of Campylobacter jejuni strain types. This method readily distinguishes C. jejuni from C. coli, has a resolving power comparable to that of multilocus sequence typing (MLST), is applicable to mixtures, and is highly automated. The strain typing approach is based on high-performance mass spectrometry, which "weighs" PCR amplicons with enough mass accuracy to unambiguously determine the base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In that study the investigators concluded that Rep-PCR was able to delineate S. pneumoniae with a discriminatory power equal to that of PFGE and suggested that it could be used as a stand-alone method for this species, with the only qualification that subtype groupings were more difficult to define by Rep-PCR. MLST with ESI-MS has been successfully used to type isolates of Streptococcus pyogenes, Acinetobacter baumannii, and Campylobacter species (8,9,13,21,38).…”
Section: Discussionmentioning
confidence: 99%
“…In that study the investigators concluded that Rep-PCR was able to delineate S. pneumoniae with a discriminatory power equal to that of PFGE and suggested that it could be used as a stand-alone method for this species, with the only qualification that subtype groupings were more difficult to define by Rep-PCR. MLST with ESI-MS has been successfully used to type isolates of Streptococcus pyogenes, Acinetobacter baumannii, and Campylobacter species (8,9,13,21,38).…”
Section: Discussionmentioning
confidence: 99%
“…General methods for PCR/ESI-MS have been described previously using the first PCR/ESI-MS instrument, the Ibis T5000 biosensor (6,12), and they remain fully applicable with the currently available instrument, marketed as Plex-ID (9). The choice of the genes used for PCR/ESI-MS analysis was primarily dictated by the location of the main mutations associated with resistance to INH and RIF (e.g., katG codon 315) and to rifampin (e.g., rpoB codons 516, 526, and 531).…”
Section: Methodsmentioning
confidence: 99%
“…To date, a variety of methods have been used to identify Campylobacter isolates to the species level. These include genotyping methods (76) such as traditional PCR (6,35,63,75), multilocus sequence typing (MLST) (5,13,38,52,67,71), amplified fragment length polymorphism (4,8,15,40), pulsedfield gel electrophoresis (PFGE) (24,62), loop-mediated isother-mal amplification (LAMP) (80,81), and microarray-based methods (73), as well as serotyping methods (21,56) and mass spectrometry (17,18,25,47,78). Typically, genotyping methods are time-consuming and require highly trained personnel.…”
mentioning
confidence: 99%